Influence of colour Doppler echocardiography on the ultrasonic assessment of congenital heart disease: a prospective study. Issue 3 (September 1991) - Gnanapragasam, J P; Houston, A B; Doig, W B; Fraser, R; Lilley, S; Murtagh, E; Olafsson, G
Abstract : OBJECTIVE--To evaluate the additional information provided by colour Doppler in the ultrasonic assessment of congenital heart disease. PATIENTS AND METHODS--A prospective study of 215 children (age range 1 day-16 years) presenting with clinical signs of congenital heart disease. RESULTS--Colour Doppler was essential for the diagnosis of an anomalous left coronary artery and altered the management of a patient initially diagnosed as having cardiomyopathy. Colour Doppler provided extra information, but without major impact on management, in the following: the diagnosis of ventricular septal defects associated with other defects, of multiple ventricular septal defects, of anomalous pulmonary venous drainage, and of mild mitral regurgitation; the demonstration of site of coarctation, of stenotic or hypoplastic pulmonary artery branches, of unobstructed flow through a right atrial membrane, and of left ventricle to right atrium regurgitation; the assessment of the width of the duct and of flow through the patent foramen ovale in transposition and tricuspid atresia; the differentiation of pulmonary atresia from critical pulmonary stenosis and the measurement of maximum velocity of tricuspid regurgitation. CONCLUSIONS--Ideally all patients should undergo colour Doppler studies before cardiac surgery to ensure a more accurate diagnosis. However, since the additional information provided does not affect the management in most patients, machines without colour Doppler can provide a satisfactory service in paediatric cardiology centres in countries where resources are limited.